2011
DOI: 10.1021/la200767e
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interactions of Mycosubtilin with Cholesterol-Containing Artificial Membranes

Abstract: Mycosubtilin is a natural antimicrobial lipopeptide produced by Bacillus subtilis strains. It is characterized by its hemolytic and strong antifungal activities. Mycosubtilin interacts with the plasma membranes of sensitive cells. However, the molecular mechanisms of its biological activities have not been completely elucidated. Our purpose was therefore to analyze the interactions of mycosubtilin with biological membranes by using biomimetic membranes such as Langmuir monolayers and multilayers. Structural ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Kenig and Abrahame (1976) reported that bacilysin hinders glucosamine synthesis, which in turn hinders cell wall synthesis. Nasir and Besson (2011) reported that mycosubtilin of B. subtilis interacts with the plasma membranes of fungal cells. Hyphal abnormalities were observed on the mycelia of Pestalotiopsis euginae treated with cell free extracts of B. subtilis that contained iturin and surfactin (Lin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Kenig and Abrahame (1976) reported that bacilysin hinders glucosamine synthesis, which in turn hinders cell wall synthesis. Nasir and Besson (2011) reported that mycosubtilin of B. subtilis interacts with the plasma membranes of fungal cells. Hyphal abnormalities were observed on the mycelia of Pestalotiopsis euginae treated with cell free extracts of B. subtilis that contained iturin and surfactin (Lin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that plipastatin did not exhibit a refractory state profile, suggesting that, like surfactin, recognition of the molecule could be independent of a specific receptor and may involve direct perception at the plasma membrane level by a lipid‐driven process (Henry et al ., ). Mycosubtilin has been shown to interact with cholesterol, ergosterol and phospholipid membrane models (Nasir and Besson, , ; Nasir et al ., ), but it is not known whether this LP could interfere with plant plasma membranes, especially by forming pores and inducing important modifications of the membrane permeability, as demonstrated for fungal membranes (Nasir and Besson, ). Physiological relevance of LP‐driven elicitation was also confirmed by the use of K‐252a, a potent inhibitor of protein kinases in animals and plants (Ruegg and Burgess, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite many works carried out on the understanding of the molecular mechanisms of biological activity of the other iturinic lipopeptides [6][7][8][9][10][11][12], there are only few limited analyses of the bacillomycin D interaction with the plasma membrane of target cells [13][14][15], and the comparison of its hemolytic activity with those of other iturinic lipopeptides did not allow us to determine a rule based on the amino acid composition of the different lipopeptides (Table 1).…”
Section: Introductionmentioning
confidence: 99%